Upaya Preventif Penyakit Jantung dengan Meningkatkan Pengetahuan Self-Management Masyarakat di Jorong Bansa - Mulyanti Roberto Muliantino; Yuanita Ananda; Rika Sarfika (Warta Pengabdian Andalas, 2023)
The COVID-19 pandemic had an impact on people living with heart disease. They often delay in control time to visit the health care unit, cancelling treatment or not continuing their medication. This condition results in decreasing health status, increasing re-current events, rehospitalization, and low quality of life. Implementation of self-management was essential in managing their disease during daily care at home. Efforts to increase the knowledge of self-management among people living with heart disease were a preventive measure to maintain their health status. These activities aimed to improve self-management knowledge among people living with heart disease in daily care. The method used group education among 22 people in the Bansa district. We used the self-management questionnaire's knowledge to measure knowledge through a pre and post-test. Data analysis was presented in descriptive statistics. The result showed an increased knowledge of self-management; the complete knowledge of self-management before education was 31.86, and after education was 43.00. Education effectively improved the knowledge of communities about self-management behaviour that can be implemented in their daily life. Continuing education is important as a preventive and persuasive strategy to increase the health status of communities.